New Report of Rhabdias sp. (Nematoda: Rhabdiasidae) from Nepal - Pun, Shyam K.; Maharjan, Mahendra (Journal of Institute of Science and Technology, 2015)
Rhabdias spp. are parasitic nematodes of amphibians and reptiles. They are distributed across wide range globally. An unidentified species of the genus Rhabdias was reported first time from the host Indian marbled toad Bufo stomaticus from Kirtipur, Kathmandu, Nepal. Journal of Institute of Science and Technology, 2015, 20(2): 153-155